Diplomacy and Education: A Changing Global Landscape - McGill Peterson, Patti (International Higher Education, 2014)
Educational diplomacy is rapidly moving beyond the realm of government sponsored initiatives to a much wider array of actors and activities. Institutions are actively developing their own brand of international relations. Governments will find it more and more difficult to dictate the nature and direction of educational diplomacy. In this baffling array of cross-border activity, senders and receivers of this kind of diplomacy need to adhere to a clear policy of mutuality if all sides are to benefit from the rising tide of global engagement.